Dietary Dill Weed (Anethum graveolens) Stimulated Disease Resistance of African Catfish (Clarias gariepinus) Against Edwardsiellosis Infection - Lee Seong Wei; Vui Kien Liew; Albaris B. Tahiluddin; Ramasamy Harikrishnan; Md. Eilious Hosain; Mohamad Nor Azra; Wendy Wee (Bacteria)
This study evaluated the effects of dietary dill weed (DW) on growth, hematological profile, digestive enzyme activities, antioxidative response, heat tolerance, gut microbiota composition, and disease resistance in African catfish (Clarias gariepinus). A control diet (basal diet) was compared to three DW diets (DW5, DW10, and DW15) with increasing DW levels (0.5, 1.0, and 1.5%, respectively). After eight weeks, fish fed DW diets exhibited significantly higher growth performance (p < 0.05) compared to the control group, as evidenced by increased final weight (FW), specific growth rate (SGR), and weight gain (WG). Conversely, the feed conversion ratio (FCR), hepatosomatic index (HSI), and visceral somatic index (VSI) were significantly lower (p < 0.05) in fish fed DW diets compared to the control. Dietary DW supplementation significantly enhanced (p < 0.05) hematological profiles, including red blood cell (RBC), white blood cell (WBC), hematocrit (HCT), and hemoglobin (HBG), compared to the control group. Similarly, antioxidant responses, including superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) activity, significantly increased (p < 0.05) in fish fed DW diets before or after the heat tolerance assay. Fish fed DW diets displayed a higher relative abundance of beneficial gut microbiota, including Cetobacterium spp., Akkermansia muciniphila, Phocaeicola spp., and Niameybacter massiliensis. Furthermore, dietary DW supplementation stimulated disease resistance against Edwardsiella tarda infection in African catfish. Regression analysis indicated that the optimal DW inclusion level for promoting growth performance and health status in African catfish ranged from 0.229 to 0.433%.